Construction of the feudal state at the time of Stefan Nemanja - Stanković Vladan D. (Baština, 2015)
The paper will seek to highlight the impact and role models who acted on policy of the Serbian state and the Stefan Nemanja as well. There, we should definitely think about Byzantium, certainly as a role model and the state that largely influenced Serbia, but we should not neglect the states from the West, for example, the famous contemporary of Nemanja, Friedrich I Barbarossa. Correspondence is conducted with the West, and in addition to the already mentioned Frederick, we have noted and brought up the correspondence with Rome. Stefan Nemanja was the founder of the Serbian state, the founder of the symphony of church and state. What will characterize the power of Stefan Nemanja is the application of feudal law and state building on the principles of the mentioned law.